High perceptual sensitivity to global motion in badminton players - Liang, Z.; Yin, D.; Liu, T.; Zhu, Z.; Lin, H.; Jin, H. (International Journal of Sport Psychology, 2021)
Global motion perception (GMP) is a fundamental aspect of visual perception. Previous studies found that action video gamers had better GMP. However, it is still under debate whether ball playing, particularly badminton playing, can improve the sensitivity of GMP. To address this issue, 24 professional badminton players, 24 sprinters and 24 non-player controls were recruited to perform a GMP task, in which participants were asked to identify the global motion direction (leftward/rightward, upward/downward, contraction/expansion, or clockwise/anticlockwise) of randomly-presented dot kinematograms. Results showed that badminton players had lower motion coherence threshold than the other two groups in radial, rotational and up/down motion forms. In left/right motion form, the threshold was lower for the badminton players than for the non-players, but the difference was not significant between badminton players and sprinters. The findings suggest that badminton training may improve the sensitivity of GMP, and this increased sensitivity is irrelevant to general physical exercise.